New access structures to scientific information: the case of Science 2.0 - Špiranec, Sonja; Babić, Ana; Lešković, Ana (2009)
Since the early 1980s, the scholarly community has been witnessing a considerable increase in the use of information and communication technologies (ICT). Specifically the use the Web has led to qualitative changes in the research community. With the advent of the Web 2.0 a new level of possible functionalities for science has been reached, leading to the concept of Science 2.0. Will the new research technology 2.0 change the way research is done and what aspects are already visible in current structures of scientific communication are questions this paper tries to answer. Several clusters of expectation emerge from the prospect of applying the principles of Web 2.0 to scientific communication, like the opening of science communities towards public and the acceleration of dissemination of scientific research through new communication and collaboration tools. In the first part the authors will comment how the Web 2.0 challenges some traditional and known structures of scientific communication and explore possibilities of applying Web 2.0 principles (collaboration, collective validation, access and generation of information) to scientific work. In the second part the authors will present results gathered through analysis of Web 2.0 services that have been integrated into academic databases and vice versa, the analysis of scientific information spaces that have been created within the Web 2.0.
Projekt MZOS
ENG